C40 THREE–DIMENSIONAL FINGER TEST: A NEW ECHOCARDIOGRAPHIC METHOD TO LOCATE THE BEST ACCESS SITE DURING NEOCHORD PROCEDURE. (18th May 2022) - Vairo, A; Alunni, G; Franchin, L; Fortuni, F; Gaiero, L; Desalvo, P; Avondo, S; Marro, M; Sebastiano, V; De Ferrari, G; Rinaldi, M; Salizzoni, S
Abstract: Background: The NeoChord procedure is a trans–ventricular, beating–heart chordal implantation for severe degenerative mitral valve regurgitation due to prolapse or flail leaflet and it is performed using a dedicated device (DS 1000 system, NeoChord, Inc. St. Louis Park, MN). The use of the transesophageal echocardiography (TEE) is crucial to guide the procedure. Bi–dimensional (2D) imaging completed with simultaneous biplane view during surgeon finger pushing on the LV wall (finger test) is currently used to choose the LV access, which is usually on the mid–distal infero–lateral wall (ILW), between the papillary muscles (PMs) at the inferior level of their insertion on LV wall. This simulation helps the operators to evaluate the safe distance to PMs to minimize the risk of damaging the sub–valvular apparatus during the insertion of the device. We aimed to compare a new 3D method with the conventional one in terms of safety and better localization of the desired entry site. Methods: During the procedure finger test has been performed with conventional 2D imaging and simultaneous biplane method. It has been completed using the real time 3D TEE placing the sample box in the bi–commissural view of the LV including the PMs and the apex. The resulting 3D volume was subsequently edited to visualize the LV from above (surgical view) to localize the bulge of the operator finger pushing on the desired segment of the LV wall. We asked the first operator, the second operator and the cardiac surgery fellow, separately, to evaluate location of their finger pushing, in terms of desired position and safety of access, both with 2D method and the 3D method to estimate the inter–operator concordance. Results: From March 2019 to September 2021 42 consecutive cases have been performed using finger test completed with 3D method without complications related to the trans–ventricular access. Regarding the choice of the right and safe entry site, the percentage of agreement between operators was higher using LV real time 3D rendering compared to the conventional finger test [82 + 21% Vs 59% + 29%, IC 95%, p: 0, 04]. Conclusion: Three–dimensional finger test is easy to perform and decreases inter–operator variability of image interpretation facilitating the surgeons to choose the best entry site in term of anatomical localization and safety.